Walk the walk the #1 rule for real leaders - Deutschman, Alan. (Brilliance Audio, 2009)
According to Deutschman, leadership really has only two elements: what one says and what one does. He also argues that most leader focus too much on words and not enough on setting an example. Here, the author profiles a wide range of leaders who always walked the walk.
Unabridged
Keywords: Leadership